If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying -5x^{2}+ 40x = 0 Reorder the terms: 40x + -5x^{2}= 0 Solving 40x + -5x^{2}= 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(8 + -1x) = 0 Ignore the factor 5.## Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0## Subproblem 2

Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8## Solution

x = {0, 8}

| 3x+4x=14 | | -12m^2+52m-56=0 | | 18b^2-222b+540=0 | | 3x+4-6x=46 | | 9x+12y=18 | | 3(x-2)=2x-4 | | 8-3x=10-x | | 2x+9=1-3x | | (3x+2)(7x+4)=8 | | 8(x-1)=8-4(2x-3) | | 6x+8=2x-12 | | 5x-4=5+2x | | 2(x+5)-3(5-x)=10 | | 8X-6=6X | | X+10=2X | | 8x+10=66 | | 8T+13-T=4T+14 | | 3(X+2)=X | | 2(X+3)=4(X-2) | | x-3=2x+6 | | x+8=-5 | | 3x-6=18+7x | | 5t-13=12-5t | | 2(4+x)=8+3x | | 2(1-x)=3(1+2x)+5 | | 1-c=-13+-8c | | x^2+22x=0 | | c=18+.5C | | x+32=55 | | 2=.13x | | 6x^2+11x-17=-7 | | 3ab+4ac= | | 6=2X-4 | | x=66x+12 | | 6x+45=10x+13 | | 9x^2=4 | | 2x+x^2=24 | | 4x^2=49 | | x^2+12x=16 | | -3x=27 | | x^2+32=12x | | 21x=84 | | x=66x-8 | | 3p-4=2 | | p^2-2p-24=0 | | 8k^2+20k=0 | | 14x^2-3x-13=-8 | | 8c^2+16c=0 | | 11x=-99 | | 7=7X-3 | | 17=7X-3 | | 17=7X+3 | | -7=105 | | -7y=105 | | 4m=-144 | | 6x^2+2x=5.5 | | x^2+9x+1=-7 | | 3A+12=12 | | 4(y-7)=4y+15 | | -8x^2-20x=0 | | 10=10x-50 | | -4+q=20 | | 15m=3 | | 8x=x+8 | | 3x^2-20x+8=0 |